Knowledge of occupational safety by hospital cleaners and hospital managers towards HIV and other blood borne pathogens transmission in Abakaliki region in Eastern Nigeria - Anozie, Uchenna Johnpaul (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPhil)--Stellenbosch University, 2015.